2012
DOI: 10.1016/j.physbeh.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary conditions and highly palatable food access alter rat cannabinoid receptor expression and binding density

Abstract: Endogenous cannabinoid signaling, mediated predominately by CB1 receptor activation, is involved in food intake control and body weight regulation. Despite advances in determining the role of the CB1 receptor in obesity, its involvement in the driven nature of eating pathologies has received little attention. The present study examined CB1 receptor alterations as a consequence of dietary-induced binge eating in female Sprague Dawley rats. Four control groups were used to control for calorie restriction and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 71 publications
8
20
0
Order By: Relevance
“…Such alteration induced by FR may depend, in turn, on the reduced Food restriction and synaptic plasticity in rat hippocampus G Talani et al surface expression of CB1Rs as indicated by western blot analysis that revealed a reduction in CB1R protein level in a hippocampal-enriched membrane preparation. These results are also in line with previous studies showing a decrease in CB1R mRNA levels in the cingulated cortex as a result of FR or palatable food consumption in rats (Bello et al, 2012). In our experimental condition, CB1R protein expression appears independent on the time point relative to food presentation, and in fact its levels were decreased at all tested times.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such alteration induced by FR may depend, in turn, on the reduced Food restriction and synaptic plasticity in rat hippocampus G Talani et al surface expression of CB1Rs as indicated by western blot analysis that revealed a reduction in CB1R protein level in a hippocampal-enriched membrane preparation. These results are also in line with previous studies showing a decrease in CB1R mRNA levels in the cingulated cortex as a result of FR or palatable food consumption in rats (Bello et al, 2012). In our experimental condition, CB1R protein expression appears independent on the time point relative to food presentation, and in fact its levels were decreased at all tested times.…”
Section: Discussionsupporting
confidence: 93%
“…Expression of CB1R protein has been found to be markedly affected by specific dietary schedules (Dazzi et al 2014;Bello et al, 2012). In the present study, immunoblot analysis revealed that the amount of CB1R protein in the whole hippocampus was significantly decreased in FR rats killed at different time points with respect to food presentation when compared with CTRL animals (one-way ANOVA and Newman-Keuls test: F (6,50) = 5.038, Po0.001; Figure 3a and b).…”
Section: Expression Of Cb1r Ecbs and Bdnf Protein In The Hippocampusupporting
confidence: 54%
“…Furthermore, hypercaloric diets have been linked to alterations in the expression and density of several components of the ECS in the brain and peripheral tissues. Thus, access to a highly palatable diet could modify the expression and density of CB1 receptors in specific brain regions [32]. It has been also demonstrated that a chronic high-fat diet exposure alters the levels of endocannabinoids and their metabolic enzymes in the pancreas and adipose tissue [33].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, either species differences, task differences, or differences in feeding conditions could account for the different effects of a CB1 receptor antagonist on fear extinction. Notably, food restriction can affect the levels of endocannabinoids and CB1 receptors (Hanus et al , 2003; Bello et al , 2012), and this may change the effects of a CB1 receptor antagonist at the CB1 receptor. It is unclear which feeding conditions more closely resemble the human condition, although it is possible that the normal function of CB1 receptors in humans maintaining stable body weights more closely resembles that seen in our food restricted rats.…”
Section: Discussionmentioning
confidence: 99%